Exploring work-related experiences of correctional officers in the Namibian correctional service - Chipango, Diana Manga (My University, 2016)
Correctional agencies worldwide have gradually moved away from the traditional intervention of imprisoning convicted persons towards a more rehabilitative objective of helping prepare inmates through social reintegration into society which has led changes in roles within the correctional agencies. The study aimed at understanding some of the contributing factors to the work- related experiences encountered by correctional officers. A qualitative research approach was applied. A narrative research design was used to explore the experiences or 14 participants, who had been identified through non-probability volunteer sampling procedure. For triangulation purposes, four key informants were also interviewed. Semi-structured interview schedules were used to collect data during the one-on-one interviews. The data was then analysed using thematic analysis. Results from the study revealed that socioeconomic factors such lack of employment opportunities, personal interest to the uniform, lack of financial support to study further as the major contributing factors to becoming correctional officers. Furthermore, factors such as lack of resources, lack of support from supervisors and management, lack of work related skills, role demands and lack of participation in decision making were identified as the challenges encountered by correctional officers. In managing the work-related challenges, the coping mechanisms used by correctional officers include self-motivation, acceptance of the situation, suppression, and peer group support. The main recommendations emanating from the study included training of correctional officers to help enhance their skill capacity, involvement of occupational social work practice in the Namibian Correctional service and embarking on research to be better understand the governing of corrections.
A report on a study project presented to The Department of Social Work School of Human and Community Development Faculty of Humanities In partial fulfillment of the requirements for the degree Masters of Art in Occupational Social Work 9 June 2016
Keywords: Correctional institutions